Pemodelan Unified Modeling Language Sistem Informasi Enterprise Resource Planning - Fatmasari Fatmasari; Siti Sauda (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Modeling is one of the techniques used to describe how information systems will be created and produced. Modeling itself can be used as a reference in the process of developing information systems to suit user needs. One modeling technique that is often used is to use a unified modeling language (UML). Modeling techniques with UML are able to describe various features of information systems. for this reason, in this research a model for the PTPN VII enterprise resource planning (ERP) information system is used as an initial step in fulfilling information management needs. the use of modeling itself is an initial implementation of information technology and information systems in a corporate environment, especially PTPN VII. The results of modeling have been done using three types of diagrams in UML as a reference in the development of structure diagrams created using class diagrams, behavior diagrams created using use case diagrams, and interaction diagrams created using activity diagrams. The results of the modeling have also been implemented in the form of a prototype of the information system so as to provide a clear picture for interested parties if the development of enterprise resource planning (ERP) information systems, especially in the PTPN VII environment. The information system prototype can also describe the initial forms for stakeholders if changes are to be made